Menetapkan Langkah dalam Kemelut: Revolusi di Kerajaan Padang - Yushar Tanjung (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2021)
This paper aims to examine the events of the social revolution and its consequences in the kingdom of Padang, Tebing Tinggi after independence during the Tengku Hasyim era. This study is analyzed using library research methods and field research with a historical approach through heuristic techniques. From the results of the study, information was obtained that the last King of the Kingdom of Padang was Tengku Hasyim, who was one of the prominent freedom fighters who stated that the Padang Kingdom was within the territory of the Republic of Indonesia. During the time of Tengku Hasyim, two important events occurred, namely Indonesian independence. Then the Social Revolution at Tebing Tinggi. Tengku Hasyim's political stance was to fully support the independence of the Republic of Indonesia and surrender the Kingdom of Padang to become part of the Republic of Indonesia. However, this did not make him immediately free from the anger of the masses who were against traditional power. In 1946, the "Social Revolution" occurred in the Kingdom of Padang which resulted in the elimination of the power of this kingdom and other Malay kingdoms in East Sumatra in a bloody event. He survived with the help of the royal family from Tanjung Kasau and when the Kingdom of Padang was under the government of the Republic of Indonesia, Tengku Hasyim held the position of Ambtenaar Bestuur Aangelegenhedeen (ABA) or mayor in 1947-1950.